A systematic review in recycling/reusing/re-manufacturing supply chain research: a tertiary study. Issue 6 (2nd November 2021) - Sinha, Sudipta; Modak, Nikunja Mohan
ABSTRACT: The present work presents a review of literature reviews in the area of recycling/reusing/re-manufacturing supply chain research. It also highlights the contribution of the review papers published in this area. To collect the sample, we use the well-reputed search engine: SCOPUS and then screening it categorically and descriptively to finalise the sample for the study. A category, impact, and topic-related classification schemes are developed, and the 67 review works existed in our final sample are discussed in the light of these classification schemes. Sustainability has three different facets: environmental, economic, and social. Achieving sustainability for enhancing the quality of the environment, cost-effective economic concern, and benefit of society is the priority in most of the articles. The study identifies several emerging issues like ways of utilisation of food and vegetable waste, ways of collection of rare earth metals from secondary sources, integration of reverse and forward supply chain, sustainable smart and flexible production system, etc., to give higher preferences for future research. The classification framework presented in this article may assist researchers to realise research gaps and help them in writing high-quality research work in the future.